Práticas baseadas em evidências na rede regular de ensino do estado de Santa Catarina: uma aproximação a partir dos saberes dos professores e de práticas com evidência de efetividade - Santos, Mariele Neli Finatto Vasselai dos (2022)
The literature on the educational inclusion of students with autism has shown that teachers are still unaware of the disorder, which leads to ineffective teaching practices. On the other hand, some teaching practices may resemble Evidence-Based Practices (EBP) in containing their active components, but without due fidelity in implementation. Active ingredients are considered the main components of comprehensive treatment packages for people with autism. The current project sought to determine how closely classroom teachers' teaching practices in the regular education system of the State of Santa Catarina, Brazil resemble the EBPs described by the American institute National Clearinghouse on Autism Evidence and Practice (NCAEP). The participants were support teachers from the Santa Catarina state school system who work directly in classes where students diagnosed with Autism Spectrum Disorder (ASD) are enrolled. Support teachers are professionals specialized in special education who work as coregents with the regular teachers of the early grades or provide assistance to teachers of subjects in the upper grades. This study combines qualitative and quantitative research, using the Derivative Exploratory Sequential Design (DEXPLOS). Divided into two stages, this study relied on qualitative data collection and, later, quantitative data collection. The qualitative stage aimed to identify PBEs used by teachers in their teaching practices so that excerpts from their answers could be used to compose vignettes for the instrument used in the quantitative phase of this study. The qualitative data were collected from the Instrument for the Investigation of Teaching Practices (I-FITP) and deepened through semi-structured interviews, both carried out with a representative, non-probabilistic sample of support teachers working in the State of Santa Catarina. A larger study's quantitative phase involved presenting the vignettes to the teachers and asking them to answer an objective questionnaire about how much they actually use the presented practices. The quantitative data were collected from the EBP Research Instrument (IFITP) Measurement Tools, which were applied to a sample that represents the universe of support teachers who serve students with ASD in the Santa Catarina state educational system. Data analysis was based on Bardin's content analysis (2011) and descriptive statistics. The results were presented according to the DEXPLOS design: qualitative, quantitative, and mixed methods. The qualitative results, obtained through the report of 11 teachers through the I-IPD instrument, indicated the use of 12 PBEs in the school context, which composed the I-FITP instrument through illustrative vignettes. The quantitative results, analyzed from 72 responses obtained through the I-FITP instrument, indicated that 16 EBPs are used by teachers in the school context, with Antecedent-Based Intervention, Modeling, Differential Reinforcement, and Promptings as the most used practices, and Video Modeling as the least used practice. The mixed-methods results detailed the teachers' use of PBEs, indicating that they are not followed according to their fidelity protocols.